2008
DOI: 10.2134/agronj2006.0363
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pasture Biomass with the Normalized Difference Vegetation Index from Active Ground‐Based Sensors

Abstract: Calculating forage availability is challenging for managers of grazing systems due to the spatial heterogeneity of swards. Remote sensing applications may help to overcome this problem through estimates of biomass made with reflectance data. The objectives of this study were to (i) estimate herbage mass using an active, on‐the‐go, ground‐based, narrow band sensor to calculate the normalized difference vegetation index (NDVI), (ii) determine if NDVI may be used to assess spatial variability of herbage mass of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The Normalized Difference Vegetation Index (NDVI), Optimized Soil Adjusted Vegetation Index (OSAVI), Renormalized Difference Vegetation Index (RDVI), Red Edge Inflection Point (REIP), and Normalized Difference Red-Edge Index (NDREI) were chosen to be comparable to previous studies. 7,36,[59][60][61] In addition, the VIs listed in Table 3 were calculated from narrowband data acquired by the ASD (with 670 nm as red, 550 nm as green, and 480 nm as blue band) to evaluate the VI RGB obtained by the UAV's camera.…”
Section: Field Spectroradiometer-derived Vegetation Indicesmentioning
confidence: 99%
“…The Normalized Difference Vegetation Index (NDVI), Optimized Soil Adjusted Vegetation Index (OSAVI), Renormalized Difference Vegetation Index (RDVI), Red Edge Inflection Point (REIP), and Normalized Difference Red-Edge Index (NDREI) were chosen to be comparable to previous studies. 7,36,[59][60][61] In addition, the VIs listed in Table 3 were calculated from narrowband data acquired by the ASD (with 670 nm as red, 550 nm as green, and 480 nm as blue band) to evaluate the VI RGB obtained by the UAV's camera.…”
Section: Field Spectroradiometer-derived Vegetation Indicesmentioning
confidence: 99%
“…Vegetation biomass estimation based on remote sensing is important for remote sensing applications [44]. Several studies have shown strong correlations between biomass and vegetation indices [45]. In particular, typical steppe vegetation indices, calculated based on the TM red and near-infrared bands, are strongly correlated with aboveground biomass [46,47].…”
Section: Correlation Between Total Aboveground Biomass and Savi In Qumentioning
confidence: 99%
“…These sensors have been used to determine biophysical parameters, such as the green BM and leaf area index (LAI) (Flynn et al . ; Fitzgerald ), and the nitrogen (N) status (Hong et al . ; Tremblay et al .…”
Section: Introductionmentioning
confidence: 99%